Agricultural change and resilience: Agricultural policy, climate trends and market integration in the Mexican maize system. (September 2018) - Eakin, Hallie; Sweeney, Stuart; Lerner, Amy M.; Appendini, Kirsten; Perales, Hugo; Steigerwald, Douglas G.; Dewes, Candida F.; Davenport, Frank; Bausch, Julia C.
Highlights: We present a systemic, multi-scalar analysis of the drivers and outcomes of the Mexican maize system in face of multiple stressors. Domestic policy reforms, rather than climatic factors or market dynamics, have been primary drivers of change. Maize persistence underscores its multifunctional nature and role in domestic food security; domestic policy needs to reflect these functions. Results highlight the influence of domestic policy, in addition to exogenous global stressors, in the resilience of the maize system. Abstract: Ensuring that national food systems have capacity to withstand volatility and shocks is a growing concern. Given the complex processes involved, multi-scalar, multi-stressor analyses of critical food systems are needed. This paper presents a multi-scalar analysis of the Mexican maize system to provide insight into the sector's evolution. The literature suggests that, over the last 30 years, climate trends, domestic and international market dynamics, and domestic policy changes have affected Mexico's maize sector. In contrast, this study finds no conclusive evidence of wide-spread abandonment of maize. In addition, while economic globalization and climatic changes are often presented as the primary drivers of change in Mexico's maize sector, results of this study show that domestic policy has been equally, if not more, influential in the sector's evolution. More than international market integration, the relatively recent geographic concentration of commercial supplies within Mexico has increased national sensitivity to idiosyncratic shocks affecting the dominant supply region. In this light, smallholder persistence across Mexico may represent an underutilized strategic asset in policy efforts to enhance both domestic food security and national-level resilience. The Mexican case illustrates the potential role for proactive domestic policy in shaping sensitivities in the national food system to both internal and exogenous shocks.